Empowering women’s capacity for improved livelihoods in non-timber forest product trade in Cameroon - Awono, A.; Ndoye, O.; Preece, L. (2010)
In Cameroon, women as the primary gatherers and traders of non-timber forest products (NTFPs) have limited access to processing technologies, marketing strategies and market information. The objective of this paper is to explore how CIFOR research and capacity building implemented from 2000 have been perceived by Cameroonian traders. An evaluation of the program took place in 2006 with thirty-eight traders out of seventy-two traders trained. Of the traders initially interviewed, 95 percent of them were women. Eighty-one percent of traders said their incomes increased as a result of the training received, 11 percent of traders mentioned a negative impact and 8 percent reported no impact. The average increase in income for those who benefited was 55 percent. The quantity of, and revenues obtained from, NTFPs increased from 2003 to 2004, but declined in 2005. These changes were related to decline or growth in gathering NTFPs, changes in demand, increased competition in the marketplace and poor health of the traders. The revenue gained from NTFPs was used for basic household needs—school fees, food and health costs. Investments in home improvements and household goods were also popular, but many traders also invested in phones, televisions and radios. These results indicate that a capacity building programme could reduce the constraints faced by traders by providing them with marketing information, accounting tools and processing and storage technology skills. A cost effective market information system could then be developed and scaled up.